Anthropometric characteristics of elite female junior rowers - Bourgois, J.; Claessens, A. L.; Janssens, M.; van Renterghem, B.; Loos, R.; Thomis, M.; Philippaerts, R.; Lefevre, J.; Vrijens, J. (Journal of Sports Sciences, 2001)
During the 1997 Federation Internationale des Societes d'Aviron (FISA) World Junior Rowing Championships, the anthropometric characteristics of 245 female junior rowers aged 17.5 +/- 0.8 years (mean +/- s) were assessed. Twenty-seven body dimensions (body mass, 6 heights or lengths, 4 breadths, 10 girths and 6 skinfolds) were measured in total. The elite female junior rowers were taller (174.5 +/- 6.2 cm) and heavier (69.5 +/- 6.2 kg), with greater length, breadth and girth dimensions, but lower skinfold thicknesses than a representative sample of Flemish (Belgian) girls of the same chronological age. An anthropometric profile chart was constructed that was rowing-specific and norms were established. Compared with scullers, sweep rowers were heavier (+4.2 kg) and taller (+2.8 cm), with greater length, breadth (except for femur width) and girth dimensions (except for calf girth). Sweep rowers also had greater skinfold thicknesses (except for the thigh and calf skinfolds). Finalists were heavier (+3.6 kg) and taller (+3.9 cm), with greater length, breadth (except for femur width) and girth dimensions (except for calf girth) than non-finalists. No significant differences were found for skinfold thicknesses between finalists and non-finalists.